Perbedaan Pengaruh Latihan Pliometrik Depth Jump Dan Squat Jump Terhadap Lompat Jauh Gaya Jongkok Siswa Di SMK Negeri 1 Geneng - Permanasari, Wafqi Rizky Nur, Yulisna Mutia Sari, SSt. Ft, M. Sc (GRS) (2016)
Plyometrics is a type of exercise training designed to produce fast, powerful movements, and improve the function of the nervous system, generally for the purpose of improving performance in sports. Plyometrics training goal is to increase the power of the next movement by using both natural and elastic components of the muscle, and tendon and stretch reflex. In plyometrics exercises, there are several methods that can be used to increase leg muscle strength among other things is depth jumps and squat jumps. Of the two methods of practice I'm interested to examine whether there are differences in the effects of exercise plyometrics depth jump and squat jump to leap away in the long jump squat style.